Application of ultrafiltration and electrodialysis techniques in lactic acid removal from whey solutions - Oberherr, Renata; Tassinary, Renata Fioravante; Vognach, Letícia; Stulp, Simone (Eclética Química, 2019)
Due to the biotechnological value of whey, this work aims at applying the ultrafiltration (UF) and subsequently the electrodialysis (ED) techniques in pilot scale plant. Whey (5% concentration) was treated twice by the UF technique, with a pressure of 4 bar (flow mode 20 L h-1). The permeate obtained was submitted to the ED process, in which 12 V were applied for 4 h. In order to evaluate the UF, parameters as turbidity, color, TOC and pH were measured. Regarding the ED technique, parameters as pH, conductivity, calcium, sodium and lactic acid concentration were evaluated. The electrodialysis unit was operated on a constant voltage, and tested the range was from 3 to 12 V. After the UF and ED processes, the pH remained unchanged. Thereafter the UF treatment, the initial turbidity was reduced by 99.9%. In terms of parameter reduction after ED, the calcium concentration was decreased in 36.0% soon after UF and ED treatments, and the lactic acid concentration in 80.0%. These results point to the possible combination of UF and ED to treat the whey and signals the potential of further using the resulting solutions as inputs in new applications in the food industry such as lactose.